Предмет: Математика,
автор: тимончик01
Заранее спасибо
(6,2x + 9,3)(4x - 3,6) = 0
Ответы
Автор ответа:
0
6,2x+9,3=0
6,2x=-9,3
x=-1,5
4x-3,6=0
4x=3,6
x=0,9
6,2x=-9,3
x=-1,5
4x-3,6=0
4x=3,6
x=0,9
Автор ответа:
0
думаю,так
Автор ответа:
0
(6,2х+9,3)(4х-3,6)=0
6,2х+9,3=0 или 4х-3,6=0
6,2х=-9,3 4х=3,6
х=-9,3:6,2 х=3,6:4
х=-1,5 х=0,9
Ответ:-1,5;0,9
6,2х+9,3=0 или 4х-3,6=0
6,2х=-9,3 4х=3,6
х=-9,3:6,2 х=3,6:4
х=-1,5 х=0,9
Ответ:-1,5;0,9
Похожие вопросы
Предмет: Физика,
автор: zhanym0501
Предмет: Информатика,
автор: Aishdjsn12
Предмет: Алгебра,
автор: ubeysyabeach
Предмет: Биология,
автор: LEVmail
Предмет: Математика,
автор: дашенька6